2009
DOI: 10.1111/j.1466-7657.2008.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dissonance towards the smoking habit among nursing and physiotherapy students at the University of Balearic Islands in Spain

Abstract: The results of this study will contribute to develop an anti-smoking programme at the university and to establish smoking-prevention campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
4
7
1
2
Order By: Relevance
“…The mean value is superior than the results from two studies carried out amongst Medicine students (26.1%) and Physiotherapy and Nursing students (27.3%), in 2009 and 2011, respectively [35,36]. However, worldwide studies have reported a prevalence of smoking amongst university students with a similar range of consumption as we present in this study.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…The mean value is superior than the results from two studies carried out amongst Medicine students (26.1%) and Physiotherapy and Nursing students (27.3%), in 2009 and 2011, respectively [35,36]. However, worldwide studies have reported a prevalence of smoking amongst university students with a similar range of consumption as we present in this study.…”
Section: Resultscontrasting
confidence: 87%
“…The established significant differences, where the highest prevalence of consumption was reported by males and particularly by males from group C, follow previous reports [35]. However, the percentage of women who consumed illegal drugs cannot be considered as low, since a third percent of them appeared to take a drug of some kind.…”
Section: Resultssupporting
confidence: 87%
“…The overall percentage of smokers found was 24Á3%. The prevalence of tobacco use among nursing students has been extensively studied and the rates found have varied by country and time period (Villar et al 2004, Suzuki et al 2005, Staib et al 2006, AlberdiErice et al 2007, Fern andez Garc ıa et al 2007, Smith & Leggat 2007, Pericas et al 2009, Hirata et al 2011, Fern andez et al 2013, Moxham et al 2013, Vitzthum et al 2013. The prevalence of tobacco use among physiotherapy students has received little attention, although the few studies available show little difference from nursing students.…”
Section: Discussionmentioning
confidence: 95%
“…Among others, there were figures of 13Á5% and 28% in two studies from the USA (Patkar et al 2003, Staib et al 2006, 30Á9% in Greece (Barbouni et al 2012), 24% in Japan (Suzuki et al 2005), 17Á6% in Australia (Moxham et al 2013), 55Á6% in Peru (Chaname et al 2009), 31Á5% in Brazil (Hirata et al 2011), 41Á9% in Germany (Vitzthum et al 2013) and 48Á2% in Italy (Ficarra et al 2011). In Spain, surveys undertaken in various regions of the country have shown percentages of smokers among healthcare students of 36Á2% in 2004 (Villar et al 2004), 29Á7% and 43Á8% in 2007(Alberdi-Erice et al 2007, Fern andez Garc ıa et al 2007) and 26Á1% in 2009 (Pericas et al 2009). Nursing and physiotherapy students have an influential role in smoking prevention (Fern andez Garc ıa et al 2007, Moxham et al 2013.…”
Section: Introductionmentioning
confidence: 94%
“…Para lograr este objetivo es necesario que dicha población universitaria no sólo conozca, sino que también practique un estilo de vida saludable [3][4] . Sin embargo, la etapa universitaria ha sido señalada como una fase de cambios en los que la práctica de AF suele verse reducida 5 y los hábitos alimenticios se ven afectados negativamente 6 , especialmente en la población femenina.…”
Section: Introduccionunclassified